Komparasi Pengolahan Data Keuangan Manual Dengan Pengolahan Data Keuangan Menggunakan Zahir Accounting Versi 5.1 - Riestiawan, Riestiawan; Ariyati, Indah (Journal of Students‘ Research in Computer Science, 2022)
The development of information technology has penetrated all areas of life in all parts of the world, which is triggered by the increasing complexity of business activities and the increasing need for financial information. Processing of financial data on CV. Akbar Motor is recorded manually using sheets of paper so that the recording still does not work optimally. In addition, manual data processing is quite time-consuming, labor-intensive, and large costs which causes late financial statements. Researchers process financial data manually then continue using Zahir Accouting Software Version 5.1 as a comparison. The research methods used in collecting data consist of observations, interviews and literature studies. Comparison between manual processing of financial data with Zahir Accounting version 5.1. aims to find out the financial condition of an enterprise in a certain period in the hope that it can be used in decision making quickly and accurately.